Thinking forward: 3-D printing in orthodontics - Shetty, Shreya K; Ahmed, Nausheer; Urukalan, Haritha; Nikhil P M; Younus, Abrar; Bhat, Ranjan K R (IP Indian Journal of Orthodontics and Dentofacial Research, 2021)
Advancements in the field of digital technology has vastly influenced various industries including dental practice. 3-D printing is one such development that has revolutionized the manufacturing industry and has become a subject of great interest in the field of dentistry. With the greatest advantage of 3-D printing being customization, it has become an important tool in delivering precise appliances and surgical guides. This article reviews the applications and incorporation of 3-D printing technology and recent advances applicable into dental practice, oral surgery and orthodontics.